2016
DOI: 10.1080/19443994.2016.1191778
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic granulation with petrochemical wastewater in a sequencing batch reactor under different operating conditions

Abstract: The aim of this study was to define the best operating conditions for the successful start-up of a granular sludge sequencing batch reactor (GSBR) treating petrochemical wastewater (PW) produced by the integrated gasification combined cycle and characterized by high NH4+-N concentration (up to 630 mg/L). Two different start-up strategies were applied during Phases A and B, using different shear forces, inoculum source and pH. The GSBR was fed with a mixture of synthetic medium and real wastewater, and a readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…were comparable with those achieved in previous studies with simulated and real industrial wastewaters [17,[29][30][31], landfill leachates [11,32] and different anaerobic digestates: in particular, Cydzik-Kwiatkowska et al [14] reported SVI 5 values within the range of 25-30 mL g TSS −1 in a GSBR treating diluted and undiluted anaerobic digester supernatant at different cycle lengths (6, 8, 12 h); Świątczak et al [6] reported SVI of about 50 mL g MLSS −1…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…were comparable with those achieved in previous studies with simulated and real industrial wastewaters [17,[29][30][31], landfill leachates [11,32] and different anaerobic digestates: in particular, Cydzik-Kwiatkowska et al [14] reported SVI 5 values within the range of 25-30 mL g TSS −1 in a GSBR treating diluted and undiluted anaerobic digester supernatant at different cycle lengths (6, 8, 12 h); Świątczak et al [6] reported SVI of about 50 mL g MLSS −1…”
Section: Resultssupporting
confidence: 87%
“…The highest FA concentration measured in our GSBR at the beginning of the cycle was approximately 5 mg N L −1 . However, no significant NOB inhibition was observed, likely due to the occurrence of different factors like prolonged biomass exposure to high ammonium (and FA) concentrations which may have favoured NOB acclimation; the granular layered structure, which may have preserved NOB from relatively high FA concentrations in the bulk liquid due to diffusion limitation, as previously observed with other toxic and inhibiting compounds [17,29,38]; a drop of initial FA concentration due to biomass activity and air stripping, which may have reduced its inhibiting potential.…”
Section: Resultsmentioning
confidence: 78%